IPTEKS PENGELOLAAN PENDAPATAN JASA PARKIR PADA PT. ANGKASA PURA I (PERSERO) BANDAR UDARA SAM RATULANGI MANADO - Languju, Cicilya; Rumagit, Rivaldo; Mawikere, Lidya (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
Management is the same as management, namely mobilizing, regulating and directing human efforts to effectively utilize materials and facilities to achieve a goal. Income is the amount of money received by the company from its activities, a large part of the sale of products and / or services to customers. Parking is an immovable condition of a vehicle that is temporary because it is abandoned by the driver. Legally prohibited from parking in the middle of the highway; But roadside parking is generally permitted. Parking facilities are built together with most buildings, to facilitate vehicles using buildings. Including in the sense of parking is any vehicles that stops at certain place whether expressed with traffic signs or not, and not solely for the purpose of raising and or reduce people and or goods. While levies according to Law no. 28 of 2009 is a regional levy as payment for services or special permits that are specifically provided and / or provided by the Regional Government for personal or agency interests. Parking revenues are expected to increase regional contributions through local taxes. The more parking revenue, the more regional contribution through the regional tax.Keywords ; Management, Income, Parking, Regional Levies